Development of Micro Small-Medium Business in Asian Countries (Indonesia, Malaysia, Philippines, and Thailand): A comparison in accounting behavior - Anggadini, Sri Dewi; Luckyardi, Senny; Surtikanti, Surtikanti (Journal of Eastern European and Central Asian Research (JEECAR), 2023)
This study examines how to support and improve micro, small, and medium enterprises (MSMEs) in ASEAN countries, which have been hit hard by the COVID-19 pandemic. This study employs a qualitative research method, which emphasizes observing and examining the substance and meaning of the phenomena more deeply. The research found that the success of MSMEs in Indonesia depends on factors like the business sector, size, financial management, and digital technology use. Similarly, MSMEs policies in Malaysia, Philippines, Thailand, and Indonesia can help increase state income, but require investment in areas like human resources, finance, and marketing. The study aims to provide insights into the strengths and weaknesses of MSMEs in these countries to help promote their development.